2000
DOI: 10.1007/s005860000141
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of the New Zealand white rabbit lumbar spine: a physiologic characterization

Abstract: IntroductionThere are many variables that affect the results of lumbar fusions. Particularly with the advent of novel methods of instrumentation and the purification of bone-stimulating growth factors, the orthopedic surgeon is faced with many surgical options. Objective comparison of these many variables is imperative. Not only must existing fusion modalities be critically evaluated, but novel modalities must also be compared to those already in use.Outcome studies are an ideal way to compare the efficacy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 20 publications
5
25
0
Order By: Relevance
“…The range of motion of our single test specimen compares well with the data from Grauer et al (2000). Both studies tested to 0.27 N m and our L3-4 motion segment had 10.61 in flexion and 5.01 in extension compared to respective means of 12.11 and 5.91 for L4-5 in their study.…”
Section: Article In Presssupporting
confidence: 56%
See 3 more Smart Citations
“…The range of motion of our single test specimen compares well with the data from Grauer et al (2000). Both studies tested to 0.27 N m and our L3-4 motion segment had 10.61 in flexion and 5.01 in extension compared to respective means of 12.11 and 5.91 for L4-5 in their study.…”
Section: Article In Presssupporting
confidence: 56%
“…Both studies tested to 0.27 N m and our L3-4 motion segment had 10.61 in flexion and 5.01 in extension compared to respective means of 12.11 and 5.91 for L4-5 in their study. In our study, the total neutral zone was 1.11 compared to 13.81 in the Grauer et al (2000) study. One explanation for this large difference may be that the inherent properties of a stepwise loading protocol result in a larger neutral zone than a continuous loading protocol (Goertzen et al, 2004).…”
Section: Article In Pressmentioning
confidence: 59%
See 2 more Smart Citations
“…The biological graft healing environment accurately reflects that of humans, as evidenced by comparable nonunion rates using autograft [122,123]. In addition, studies have shown the rabbit lumbar spine exhibits a similar physiological range of motion to the human spine [124] with kinematic characteristics that are useful for the evaluation of posterolateral spinal fusion [125]. However, the model has a number of limitations:…”
Section: Challenges To Clinical Translationmentioning
confidence: 96%